A qualitative study on usage of social media among PR practitioner during Covid-19 pandemic in Malaysia - Lee, Brianna; Tai, Christine Xin Jie; Tan, Joanne Xin Yi; Liew, Shir Ying; Loo, Xin Rong (2022)
As Covid-19 pandemic happened, social media had been defined as one of the important communication tools that frequently used in the workplace, especially for public relations practitioners. People used social media to continue communicating and socializing with others even there are some consequences brought by social media. A qualitative research approach will be conducted to explore the impact of social media usage among public relations practitioners and investigate the social media usage among public relations practitioners so that they are able to provide public relations practitioners a better understanding about how they can use social media strategically to further the organization’s goals and objectives. As such, 5 public relations practitioners from non-government PR agencies in Malaysia were sampled. In-depth interview method was chosen for this research study while thematic analysis methodology used to analyze the data collected by the samples. Through the thematic analysis, we found that there are seven usages and nine impacts of social media among the PR practitioners during the Covid-19 pandemic. The discussion has been made by referring to the other journal studies and there are some similarities and differences compared to the other studies.